Kemampuan Mengidentifikasi Unsur Intrinsik Cerita Dongeng dalam Pembelajaran Menulis Karangan Siswa Kelas II MI Miftahul Ulum Menganti - Novitasari, Ratna; Prameswari, Noviardani Kartika; Azminah, Suhartini Nurul (Medan Resource Center, 2023)
This research investigates Class II students' proficiency in identifying intrinsic elements of fairy tales during essay writing at MI Miftahul Ulum. Utilizing a qualitative descriptive approach, data was gathered through observation, interviews, questionnaires, and documentation. The findings reveal enhanced intrinsic element identification skills among students when teachers incorporate fairy tale visuals into the teaching process. This visual aid not only provides a realistic depiction but also stimulates self-motivation, contributing positively to students' learning progress. However, challenges persist, including difficulties in determining story themes, character names, traits, plot development, and story messages. These challenges are attributed to the prevalent use of traditional lecture-focused methods in Indonesian language teaching, a lack of emphasis on student activities, and an overall deficiency in enthusiasm for learning. Addressing these challenges is crucial to improving students' comprehensive understanding of intrinsic elements in fairy tales during essay writing.